Novel mechanisms of controlling the activities of the transcription factors Spo0A and ComA by the plasmid-encoded quorum sensing regulators Rap60-Phr60 in Bacillus subtilis - Boguslawski, Kristina M. (Mol Microbiol, 2015)
Bacillus subtilis and its closest relatives have multiple rap-phr quorum sensing gene pairs that coordinate a variety of physiological processes with population density. Extra-chromosomal rap-phr genes are also present on mobile genetic elements, yet relatively little is known about their function. In this work, we demonstrate that Rap60-Phr60 from plasmid pTA1060 coordinates a variety of biological processes with population density including sporulation, cannibalism, biofilm formation and genetic competence. Similar to other Rap proteins that control sporulation, Rap60 modulates phosphorylation of the transcription factor Spo0A by acting as a phosphatase of Spo0F~P, an intermediate of the sporulation phosphorelay system. Additionally, Rap60 plays a noncanonical role in regulating the autophosphorylation of the sporulation-specific kinase KinA, a novel activity for Rap proteins. In contrast, Rap proteins that modulate genetic competence interfere with DNA binding by the transcription factor ComA. Rap60 regulates the activity of ComA in a unique manner by forming a Rap60–ComA–DNA ternary complex that inhibits transcription of target genes. Taken together, this work provides new insight into two novel mechanisms of regulating Spo0A and ComA by Rap60 and expands our general understanding of how plasmid-encoded quorum sensing pairs regulate important biological processes.